Examination of Surface Conditions and Other Physical Properties of Commonly Used Stainless Steel Acupuncture Needles. Issue 2 (April 2014) - Xie, Yi Min; Xu, Shanqing; Zhang, Claire Shuiqing; Xue, Charlie Changli
Objectives: The present work examined the surface conditions and various other physical properties of sterilised single-use stainless steel acupuncture needles from two of the most popular brands widely used in many countries. Methods: Scanning electron microscope (SEM) images were taken for 10 randomly chosen needles from each brand. Further SEM images were taken after each of these needles underwent a standard manipulation with an acupuncture needling practice gel. A comparison of forces and torques during the needling process was also carried out. Results: The SEM images revealed significant surface irregularities and inconsistencies at the needle tips, especially for needles from one of the two brands. Metallic lumps and small, loosely attached pieces of material were observed on the surfaces of some needles. Some of the lumps and pieces of material seen on the needle surfaces disappeared after the acupuncture manipulation. If these needles had been used on patients, the metallic lumps and small pieces of material could have been deposited in human tissues, which could have caused adverse events such as dermatitis. Malformed needle tips might also cause other adverse effects including bleeding, haematoma/bruising, or strong pain during needling. An off-centre needle tip could result in the needle altering its direction during insertion and consequently failing to reach the intended acupuncture point or damaging adjacent tissues. Conclusions: These findings highlight the need for improved quality control of acupuncture needles, with a view to further enhancing the safety and comfort of acupuncture users.